1993
DOI: 10.1213/00000539-199377020-00011
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Spinal Anesthesia with a Microcatheter and Low-Dose Bupivacaine Decreases the Hemodynamic Effects of Centroneuraxis Blocks in Elderly Patients

Abstract: This prospective randomized study was designed to investigate the hemodynamic effects and quality of continuous spinal anesthesia (CSA) after rapid injection of a low dose of 0.5% bupivacaine through a 32-gauge microcatheter. The method was compared with continuous epidural (CEA) and single-dose spinal anesthesia (SSA). Seventy-seven elderly patients (ASA II-III) ranging from 57 to 94 yr old and undergoing lower limb surgery were assigned to CSA (n = 26), CEA (n = 26), and SSA groups (n = 25). In all three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 0 publications
3
21
0
4
Order By: Relevance
“…In some other studies comparing CSA with other neuraxial techniques, the authors found less frequent and less pronounced decreases in MAP in the CSA groups. [24] In our study, MA P values were decreased in both groups, with the significant decrease occurring first at 30 min and at 90 min in the CSA and USA groups, respectively. In Bai et al .…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In some other studies comparing CSA with other neuraxial techniques, the authors found less frequent and less pronounced decreases in MAP in the CSA groups. [24] In our study, MA P values were decreased in both groups, with the significant decrease occurring first at 30 min and at 90 min in the CSA and USA groups, respectively. In Bai et al .…”
Section: Discussionsupporting
confidence: 48%
“…[123] CSA allows titration of small amounts of local anesthetic to achieve the appropriate level and provide adequate duration of anesthesia with only minimal hemodynamic changes;[4] thus, minimizing the risks of cardiovascular and respiratory disturbances. [56] Primary indications for CSA in elderly and high-risk patients are lower abdominal and lower limb surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported improved hemodynamic control with continuous SA over epidural or single-dose SA in healthy patients (12-13). Collard et al utilized continuous SA in two patients with severe AS undergoing surgery on the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a comparison of CSA with SSA and CEA for lower extremity orthopedic surgery in elderly patients, mean arterial pressure did not change in the patients who had CSA, but in the CEA and SSA groups, mean arterial pressure dropped by 15% and 19%, respectively. 17 A recent study of elderly patients undergoing hip fracture repair compared CSA with low-dose bupivacaine SSA. In the SSA group, mean arterial pressure dropped by $30% in 51% of patients, while only 8% of patients with CSA exhibited such a change, despite receiving less ephedrine (11 mg with SSA versus 4.5 mg in CSA) to support blood pressure.…”
Section: Clinical Use Of Csamentioning
confidence: 99%